Enzymatic reactions towards aldehydes: An overview - Schober, Lukas; Dobiašová, Hana; Jurkaš, Valentina; Parmeggiani, Fabio; Rudroff, Florian; Winkler, Margit (Flavour and fragrance journal, 2023)
Many aldehydes are volatile compounds with distinct and characteristic olfactory properties. The aldehydic functional group is reactive and, as such, an invaluable chemical multi‐tool to make all sorts of products. Owing to the reactivity, the selective synthesis of aldehydic is a challenging task. Nature has evolved a number of enzymatic reactions to produce aldehydes, and this review provides an overview of aldehyde‐forming reactions in biological systems and beyond. Whereas some of these biotransformations are still in their infancy in terms of synthetic applicability, others are developed to an extent that allows their implementation as industrial biocatalysts. Nature has evolved a number of enzymatic reactions to produce aldehydes, and this review provides an overview of aldehyde‐forming reactions in biological systems and beyond.